2008
DOI: 10.1590/s1516-35982008000700006
|View full text |Cite
|
Sign up to set email alerts
|

Valor nutritivo de silagens de capim-marandu submetidas aos efeitos de umidade, inoculação bacteriana e estação do ano

Abstract: RESUMO -O estudo foi realizado para avaliar o efeito da estação do ano, do teor de matéria seca (MS) e da inoculação bacteriana sobre o valor nutritivo de silagens de Brachiaria brizantha cv. Marandu. O delineamento experimental foi o inteiramente casualizado, disposto em arranjo fatorial (2 × 3 × 3), com duas estações do ano (verão e inverno), três teores de MS (com ou sem emurchecimento ou adição de polpa cítrica peletizada, PCP) e ausência ou presença de inoculante (Lactobacillus plantarum ou Lactobacillus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 10 publications
(21 reference statements)
1
8
0
5
Order By: Relevance
“…Another factor to be taken into consideration is that the addition of dehydrated barley increased the dry matter, and by this likely favoured better fermentation of ensiled material and thus reduce the losses caused by effluent formation. These results were similar to those of Ribeiro et al (2008), who observed FVI values of 76 and 141 in a study of Tanzania grass silage with levels of 0, 8, 16, 24 and 34% wheat bran.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Another factor to be taken into consideration is that the addition of dehydrated barley increased the dry matter, and by this likely favoured better fermentation of ensiled material and thus reduce the losses caused by effluent formation. These results were similar to those of Ribeiro et al (2008), who observed FVI values of 76 and 141 in a study of Tanzania grass silage with levels of 0, 8, 16, 24 and 34% wheat bran.…”
Section: Resultssupporting
confidence: 91%
“…A similar behaviour was observed for the consumption expressed in relation to metabolic weight. Ribeiro et al (2008) estimated dry matter intaketo vary between 1.74 and 2.59% live weight for Tanzania grass silages on increase of 0 to 30% wheat bran. The initial increase in dry dry matter intake in the present study can be explained in part by the increase in dry matter content of the silage.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the literature for tropical grasses, the DM content ranges from 157.8 to 280 g/kg (Patrizi et al, 2004;Ribeiro et al, 2008;Ávila et al, 2009;Silva et al, 2011). According to McDonald et al (1991), the optimum dry matter content for good quality silages ranges from 300 to 350 g/kg.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the increase in the CHO contents with greater cutting heights, these values are considered to be low and characteristic of tropical grasses (Ribeiro et al, 2008;Ávila et al, 2009;Vasconcelos et al, 2009). However, the mean level of silage CHO was 7.2 g/kg, regardless of cutting height.…”
Section: Resultsmentioning
confidence: 99%
“…Napier, Taiwan, Merker, Porto Rico, Cameroon, Mott), Cynodon dactylon (Tifton) and the hybrid of Cynodon dactylon x C. nlemfuensis (Coastcross). (Patrizi et al, 2004;Ribeiro et al, 2008;Oliveira et al, 2007;Zopollatto et al, 2009;Lopes & Evangelista, 2010). When compared to the others, elephant grass stands out in silages researches because of present high productivity and higher soluble carbohydrates concentration.…”
Section: Tropical Grass Characteristicsmentioning
confidence: 99%